Claiming their place - Men's interactions with midwives within maternity care - LALOR, JOAN; CRONIN, PATRICIA (My University, 2012)
Over the past two decades there has been increased interest in the role of men in the childbearing and childrearing process. However, there is a dearth of evidence which specifically focuses on the role of midwives in facilitating men?s transition to fatherhood. The aim of this paper is to explore men?s experiences of their interactions with midwives during the antenatal, intrapartum and postnatal period and discuss whether these interactions impact on their transition to fatherhood. Glaser?s classic grounded theory methodology was used to theoretical sample 37 first time fathers from two large urban maternity care sites and one rural area in Ireland. Data were analysed using the constant comparitative method. The findings suggest that most men attend antenatal care appointments, although it?s not about them they do value being included by midwives. Men?s inclusion in maternity care is dependent on the maternity care staff they meet and the busyness of the hospital at that time. Both positive and negative encounters make an impact on transition to fatherhood in terms of gaining knowledge and skills necessary to increase their confidence as a father. The inclusion of men by midwives in antenatal, intrapartum and postnatal care make an impact on men?s transition to fatherhood, therefore midwives need to be cognisant of the supportive role of the father to his partner and baby.
NICER
PUBLISHED
Nottingham
Keywords: Men; Maternity